2009
DOI: 10.1159/000229781
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Determinants for Hemorrhagic Transformation of Cerebral Infarction

Abstract: Background: Frequency and associated risk factors for hemorrhagic transformation (HT), a worrying complication of ischemic stroke (IS), are not clearly defined. Our aim was to estimate the overall frequency and risk factors for HT in a hospital-based population. Methods: A retrospective review of medical records of patients discharged from our department during the period 2004–2006 with a diagnosis of anterior IS. Demographic, clinical and hematological information was collected. Uni- and multivariate logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 43 publications
(33 reference statements)
5
71
1
1
Order By: Relevance
“…Stroke severity and infarct size is the single factor that best correlates with HT. 1 Other factors include increasing age, baseline systolic blood pressure, hypertension, serum glucose, and antiplatelet use. A meta-analysis of 55 human studies reported factors associated with tPA-related HT including older age, greater stroke severity, higher glucose, atrial fibrillation, congestive heart failure, renal impairment, previous antiplatelet agents, leukoaraiosis, and a visible acute cerebral ischemic lesion on pretreatment brain imaging.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
“…Stroke severity and infarct size is the single factor that best correlates with HT. 1 Other factors include increasing age, baseline systolic blood pressure, hypertension, serum glucose, and antiplatelet use. A meta-analysis of 55 human studies reported factors associated with tPA-related HT including older age, greater stroke severity, higher glucose, atrial fibrillation, congestive heart failure, renal impairment, previous antiplatelet agents, leukoaraiosis, and a visible acute cerebral ischemic lesion on pretreatment brain imaging.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
“…4,5 HT occurs in 10% to 40% of patients with ischemic stroke 5 and is predictive of the worst clinical outcomes. 6 Our aim was to test whether LDL-C lowering with chronic PCSK9 inhibition increases the risk of HT in acute ischemic stroke.…”
mentioning
confidence: 99%
“…3 A relationship between low LDL-C levels and the risk of hemorrhagic transformation (HT) after ischemic stroke has been suggested. 4,5 HT occurs in 10% to 40% of patients with ischemic stroke 5 and is predictive of the worst clinical outcomes. 6 Our aim was to test whether LDL-C lowering with chronic PCSK9 inhibition increases the risk of HT in acute ischemic stroke.…”
mentioning
confidence: 99%
“…Inclusion criteria have been previously reported. 9,10 Briefly, all patients performed a baseline brain computed tomography (CT) scan within 24 hours from symptoms onset and a follow-up CT. Patients with transient ischemic attacks and cerebral hemorrhage were excluded.…”
Section: Methodsmentioning
confidence: 99%